A witch's guide to magical innkeeping - Sangu Mandanna (London : Hodderscape / Hodder & Stoughton Limited, 2025)
"Once, Sera Swan was one of the most powerful witches in Britain. Then she resurrected her great-aunt Jasmine from the (very recently) dead, lost most of her powers, befriended a semi-villainous talking fox, and was exiled from her Guild. Now she helps Jasmine run an enchanted inn in Lancashire, where she deals with their quirky guests' shenanigans and longs for a future that seems lost. Until she finds about an old spell that could restore her power . . . Enter Luke Larsen, handsome magical historian, who might have the key to unlocking the spell's secrets. Luke has no interest in the inn's madcap goings-on, and is even less interested in letting a certain bewitching innkeeper past his walls. So no one is more surprised than he is when he agrees to help. Running an inn, reclaiming lost power, and staying one step ahead of the watchful Guild is a lot for anyone, but Sera is about to discover she doesn't have to do alone - and that love might be the best magic of all."
Keywords: Indian English fiction